The Personality of Kurdish Poet Ahmad Nalbend (A Psychological-Analytical Study) - Naamat, Arian Tatar; Mohammad, Nasraddin Ebrahem (Perkumpulan Alumni dan Santri Mahyajatul Qurro', 2025)
This research aims to identify and analyze an aspect of the personality of Kurdish poet Nalbend (1891-1963), whose prominence emerged during the great September Revolution against the Iraqi regime of that time, and who committed suicide upon hearing news of the killing of many people in one of those attacks. To achieve this objective, a descriptive analytical method was used by researchers to collect facts and data on the current study for comprehensive interpretation and analysis. The sample consisted of 337 pages, randomly selected from 2513 pages of his poetical works (Kurds' Garden). After content analysis, results showed that nearly 2866 frequencies of depression symptoms were observed in his poetry across psychological, mental, emotional, and physical aspects, especially after the death of his son and two wives, and Kurdistan's unsuitable political conditions. His poetry contains many religious, educational, political, social, humanistic, and economic concepts. Therefore, researcher suggests that those concerned should utilize it in different stages of study as curriculum, particularly in Kurdistan universities.